Medial Tibial Stress Syndrome: Muscles Located at the Site of Pain - Ato Ampomah Brown (Scientifica)
Objective. The purpose of this study was to examine the relationship between the location of the MTSS pain (posteromedial border of tibia) and the muscles that originate from that site. Method. The study was conducted in the Department of Anatomy of the School of Medical Sciences, University of Cape Coast, and involved the use of 22 cadaveric legs (9 paired and 4 unpaired) from 11 males and 2 females. Findings. The structures that were thus observed to attach directly to the posteromedial border of the tibia were the soleus, the flexor digitorum longus, and the deep crural fascia. The soleus and flexor digitorum longus muscles were observed to attach directly to the posteromedial border of the tibia. The tibialis posterior muscle had no attachment to this site. Conclusion. The findings of this study suggest that if traction is the cause of MTSS then soleus and the flexor digitorum muscles and not the tibialis posterior muscle are the likely cause of MTSS.